Causes and Impacts of Variation Order in Building Construction Projects: A Case Study of Three Projects at Bharatpur Metro - Ghimire, Shivahari; Bohra, Niraj; Awasthi, Keshab Datt (Journal of UTEC Engineering Management, 2023)
DOI: https://doi.org/10.36344/utecem.2023.v01i01.010Variation orders are common in civil engineering construction projects and serve as significant measurement tools for project efficiency and success. This study focuses on identifying the causes and impacts of variation orders in building projects. Three hotel buildings under construction in Bharatpur were considered for the study. The study population included the client, consultant, and contractor, as they are the major stakeholders in any construction project. Data were collected using a five-point Likert scale and analyzed using the Relative Importance Index (RII) to rank the causes and impacts of variation orders. The study also identified strategies to minimize variation orders. Based on the overall ranking using the RII index, the top three causes of variation orders in building projects at Bharatpur were found to be: Errors and omissions in design (RII = 0.953), Variations in the scope of work by additions, omissions, and alterations of the employer’s requirements (RII = 0.937) and Change in design and drawings by the consultant (RII = 0.905)Regarding the impacts of variation orders, the top three identified impacts were: Completion schedule delay, Increase in project cost, Affect on progress. All parties strongly agreed on the ranking of these impacts, as supported by a Kendall’s coefficient of concordance value of 0.973.Strategies to minimize variation orders: Fourteen major strategies were identified and analyzed to minimize variation orders. The top three measures, ranked based on overall RII analysis (Kendall’s coefficient of 0.812), were; Complete the drawings at the tendering stage (RII = 0.942), All involved parties should plan adequately before works start on-site (RII = 0.937) and Carry out detailed site investigation, including soil investigations, and consider them during the tendering stage (RII = 0.895).